2014
DOI: 10.1111/jppi.12063
|View full text |Cite
|
Sign up to set email alerts
|

Successes and Challenges in the Implementation of Care Pathways in an Intellectual Disability Service: Health Professionals' Experiences

Abstract: Health care pathways are a relatively new approach to delivering care in intellectual disability services. This study aimed to ascertain and explore successes and challenges in the implementation of care pathways in a National Health Service (NHS) adult intellectual disability service in Leicestershire, United Kingdom. Data were obtained from a variety of sources including observations of multidisciplinary team (MDT) meetings, issue logs and feedback from health professionals. Constant comparative analysis ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 28 publications
1
17
0
Order By: Relevance
“…The findings show that dementia screening and pathways have become embedded within practice, providing health and social care professionals with a common framework and facilitating a co‐ordinated, efficient, multidisciplinary approach. This reflects findings from other adult learning disability services in the United Kingdom that introducing care pathways improves communication and information‐gathering, strengthens multidisciplinary working, leads to more co‐ordinated, standardised care and reduces duplication, benefiting clients (Ahmad et al., ; Wood et al., ). In the wider research literature, concerns about care pathways surround: restricting the ability to apply clinical judgement; stifling innovation and progress; and the need for leadership, good communication and time to implement pathways.…”
Section: Discussionsupporting
confidence: 60%
“…The findings show that dementia screening and pathways have become embedded within practice, providing health and social care professionals with a common framework and facilitating a co‐ordinated, efficient, multidisciplinary approach. This reflects findings from other adult learning disability services in the United Kingdom that introducing care pathways improves communication and information‐gathering, strengthens multidisciplinary working, leads to more co‐ordinated, standardised care and reduces duplication, benefiting clients (Ahmad et al., ; Wood et al., ). In the wider research literature, concerns about care pathways surround: restricting the ability to apply clinical judgement; stifling innovation and progress; and the need for leadership, good communication and time to implement pathways.…”
Section: Discussionsupporting
confidence: 60%
“…This service is integral to a tiered model of forensic ID provision (Devapriam and Alexander, 2012) that was developed as part of a wider clinical care pathway project (Wood et al, 2014). In order to successfully introduce the service, a mapping exercise was conducted to evaluate whether there were any skill gaps within the workforce.…”
Section: Study Setting and Participantsmentioning
confidence: 99%
“…The team mission, goals and guidelines for working together were outlined as part of this charter and a commitment from all members was sought. Wood et al [13], in studying the implementation of care pathways in an intellectual disability service, concluded that leadership plays an important role in guiding and supporting service delivery and managing staff reactions to change.…”
Section: Structural Supports and Team Activities To Promote And Strenmentioning
confidence: 99%